Модернизация и реконструкция энергетических установок - Богуслаев, Вячеслав Александрович; Жеманюк, Павел Дмитриевич; Морозов, Валерий Иванович; Митин, Владимир Петрович; Билошапка, Сергей Владимирович (НТУ "ХПИ", 2017)
Рассматриваются варианты создания модифицированных газотурбинных установок на базе раннее разработанных серийных блоков и агрегатов. В течение времени при эксплуатации газотурбинных установок происходит физический и моральный износ составляющих. Процесс модернизации, на сегодняшний момент, является эффективным и экономичным методом восстановления работоспособного состояния входящих агрегатов, при котором достигается увеличение ресурса изделия, повышаются его технические и эксплуатационные характеристики, улучшаются экологические показатели.

The purpose of this scientific paper is to familiarize the readers with a level of the developments and engineering opportunities of the JSC "MOTOR SICH" involved in the manufacture, modernization and reconstruction of power plants produced by the Company itself. The history of the Company lasts for more than 100 years and dates back to 1907. The Company manufactures reliable aircraft engines and gas turbine plants that are competitive in the world market. Developed and commissioned new technologies that rest on the latest achievements of science and technology, professional, highly qualified and united team, unique production base, the resources, efficient managerial strategy all that forms the platform for the success and continuous development. The JSC "MOTOR SICH" has been involved in the development of products for civil purposes starting from the mid-60ies of the last century. At that time, aircraft gas-turbine engines with expired service life were used. Later on updated gas-turbine drives were developed and their modifications are operated at the present time. From the start of production activities the company manufactured about 3000 power plants based on the latest achievements of science and technology for that time. Undoubtedly, the operation of gas turbine plants results in physical and moral wear of the components, therefore, the present-time modernization process is an efficient and sparing method of the restoration of the functional state of constituent units that allows us to extent the service life of the product, improve its technical and operating characteristics and also ecological indices.
Power plant modernization and reconstruction
Keywords: установка газотурбинная; привод двухтопливный; комплекс теплоэнергетический; система безредукторная; муфты спейсерные; gas-turbine plant; double-fuel drive; heat power system; gearless system; spacer sleeves